Implementation of Occupational Safety and Health (K3) Inspection as a Work Accident Prevention Effort in Palm Oil Factory, Kampar Regency, Riau Province - Putri Hidayah; Herniwanti; M. Kamali Zaman (Institute of Computer Science (IOCS), 2022)
Work safety issues are closely related to work accidents. Indonesia's work accident rate is still high and tends to increase yearly. The implementation of a practical occupational safety and health (K3) inspection is a preventive measure that can be taken to ensure that the work environment is always safe, healthy, and safe. Inspection is the best way to find problems and assess risks before accidents occur. This study aims to determine the implementation of Occupational Safety And Health (K3) Inspection as an Effort to Prevent Work Accidents in Palm Oil Mills in Kampar-Riau Regency in 2021. The study was from August-September, with the subjects being two workers, two factory supervisors, and 1 HES/Safety. Officer of Palm Oil Mill in Kampar-Riau Regency. This research is descriptive with a qualitative case study method by conducting field observations with the help of checklist sheets and in-depth interviews with document searches. The study results found that the company had carried out occupational safety and health (K3) inspections, which were the manager's responsibility. The company has provided facilities and infrastructure such as providing a budget for carrying out occupational safety and health (K3) program activities such as providing complete protective equipment, fire extinguishers, and first aid kits. The company already has a policy regarding Occupational Safety And Health (K3) and company policy towards workers. The OHS management system at the oil palm factory in Kampar Regency has been implemented and refers to government regulation no 50 of 2012. For companies, it is necessary to form a unique organization that oversees the implementation of the OHS program and divides tasks according to the plan with the expertise they have and is listed in the organizational structure with their respective portion.